Correlated evolution between hearing sensitivity and social calls in bats - Bohn, Kirsten M (The Royal Society, 2006)
Echolocating bats are auditory specialists, with exquisite hearing that spans several octaves. In the ultrasonic range, bat audiograms typically show highest sensitivity in the spectral region of their species-specific echolocation calls. Well-developed hearing in the audible range has been commonly attributed to a need to detect sounds produced by prey. However, bat pups often emit isolation calls with low-frequency components that facilitate mother–young reunions. In this study, we examine whether low-frequency hearing in bats exhibits correlated evolution with (i) body size; (ii) high-frequency hearing sensitivity or (iii) pup isolation call frequency. Using published audiograms, we found that low-frequency hearing sensitivity is not dependent on body size but is related to high-frequency hearing. After controlling for high-frequency hearing, we found that low-frequency hearing exhibits correlated evolution with isolation call frequency. We infer that detection and discrimination of isolation calls have favoured enhanced low-frequency hearing because accurate parental investment is critical: bats have low reproductive rates, non-volant altricial young and must often identify their pups within large crèches.